Recent NASA/GSFC cryogenic measurements of the total hemispheric emissivity of black surface preparations. Issue 1 (November 2015) - Tuttle, J; Canavan, E
Abstract: High-emissivity (black) surfaces are commonly used on deep-space radiators and thermal radiation absorbers in test chambers. Since 2011 NASA Goddard Space Flight Center has measured the total hemispheric emissivity of such surfaces from 20 to 300 K using a test apparatus inside a small laboratory cryostat. We report the latest data from these measurements, including Aeroglaze Z307 paint, Black Kapton, and a configuration of painted aluminum honeycomb that was not previously tested. We also present the results of batch-to- batch reproducibility studies in Ball Infrared Black TM and painted aluminum honeycomb. Finally, we describe a recently-adopted temperature control method which significantly speeds the data acquisition, and we discuss efforts to reduce the noise in future data.